Philosophical affiliation and freedom of thought in Roman Epicureanism: a brief discussion based on texts by Lucretius and Cicero - Calheiros de Lima, Sidney (Romanitas - Revista de Estudos Grecolatinos, 2023)
We seek to discuss how allegiance to a philosophical sect and freedom of thought are related in the context of the reception of Epicureanism in Rome, based on the analysis of passages from texts by Lucretius and Cicero. The starting point is the observation of the way in which the relationship between the persona of the poet-teacher and the authority whose doctrine he expounds is built in De rerum natura. Next, we analyze texts in which Cicero explores the relationship between the followers of the Garden and Epicurus. We try to show how the approach to this relationship serves the criticisms undertaken by Cicero against Epicureanism.
Keywords: Philosophy; Latin literature; Lucretius; Cicero